E Right ventricular origin of arrhythmias in Scn5a+/− mice is due to reduced Na+ and higher K+ channel expression and function. (16th May 2012) - Martin, C A; Siedlecka, U; Kemmerich, K; Lawrence, J; Cartledge, J; Guzadhur, L; Brice, N; Grace, A A; Schwiening, C; Terracciano, C M; Huang, C L-H
Abstract : Introduction: Brugada syndrome is associated with ventricular tachycardia originating in the right ventricle (RV); this has been attributed to either depolarisation abnormalities or increased repolarisation heterogeneities. We have used a heterozygotic Scn5a+/− murine model to investigate the underlying mechanisms for the predisposition of the RV to arrhythmias. Methods and Results: Nav 1.5 mRNA and protein expression were lower in Scn5a+/− than wild-type (WT) hearts, with a further reduction in the RV compared to left ventricle (LV) (Abstract E figure 1A, B, n=4, significant differences: * = WT vs Scn5a+/− ; # = LV vs RV). There were higher expression levels of Kv 4.2, Kv 4.3 and KChIP2 in RV than LV in both groups. Action potential (AP) upstroke velocity was decreased in Scn5a+/− (RV: 59.43±2.70 V/s to 30.26±4.03 V/s, p<0.0001, n=20), and furthermore was smaller in RV than LV. AP durations were smallest in the RV of Scn5a+/− myocytes. RV transient outward current density ( Ito ) was greater than LV in both WT and Scn5a+/− (Abstract E figure 1C, n=17), with similar voltage dependence of activation. Time constants of inactivation were larger in RV than LV, and voltage dependence of inactivation was shifted to more negative values in RV compared to LV, but to more positive values in Scn5a+/− compared to WT. Maximum Na + current density ( INa ) was decreased in Scn5a+/−, with a further reduction in the RV (Abstract E figure 2A–C, n=17). Voltage dependence of activation was unchanged, but inactivation was shifted to more negative values in Scn5a+/− . Maximum persistent Na + current density ( IpNa ) was decreased in a similar pattern to INa (RV: −0.30±0.03 pA/pF, n=15 vs −0.17±0.02 pA/pF, n=22, p=0.0009). Conclusion: Our findings show preferential upregulation of the single Scn5a gene in the LV of the Scn5a+/− mice compared to RV. The reduced expression of Na + channels in RV leads to smaller INa, resulting in slowed conduction, and smaller IpNa, which in combination with increased Ito, results in shorter AP durations and greater heterogeneity of repolarisation, thus suggesting arrhythmogenesis may be initiated by both abnormal depolarisation and repolarisation in the RV of Scn5a+/− hearts. Insight into the molecular mechanisms of arrhythmias could prove crucial in planning possible new pharmacological therapies for a disease where the mainstay of treatment is cardioverter-defibrillator implantation.